New Advanced Technologies - Lazinica, Aleksandar (IntechOpen, 2010)
This book collects original and innovative research studies concerning advanced technologies in a very wide range of applications. The book is compiled of 22 chapters written by researchers from different areas and different parts of the world. The book will therefore have an international readership of a wide spectrum.